Teaching the Neurological Examination in a Rapidly Evolving Clinical Climate - Hillis, James M.; Milligan, Tracey A. (Seminars in Neurology, 2018)
The neurological examination remains the essence of neurology. It allows symptoms to be assessed, diagnoses to be made, and dynamic functions to be followed. Skill in the neurological examination has faced increasing challenges from the encroachment of diagnostic imaging, but has maintained its clinical utility. It has also encountered the battle for the precious time within a medical curriculum. This review considers how the neurological examination can best be taught into the future. It does so by considering factors related to the examination, the learner, the teacher, and the modern clinical environment.
Keywords: clinical examination; neurology service; feedback; technology